Dynamic Distribution System Reconfiguration to Improve System Reliability Considering Renewables and Energy Storage - Cláudio Miguel Marques Pinto dos Santos (2018)
The economic development and the use of more and more technologies by the consumers make the constant energy supply and quality become a critical concern. One way to address this concern is through the implementation of automated distribution systems with intelligent technologies to improve the systems reliability and efficiency in operation. The present electrical systems are evolving due to the new functionalities that the electrical system are expected to have, namely the integration of renewable energy sources in large-scale, the integration of electric vehicles, enable smart grid technologies, among others. In this scenario, Distributed Smart Systems (DSS) should operate and restore discontinued service to consumers. In order to the system gain theses ability is necessary replace the manual switches for remotely controlled switches, improving the system restoration capability having in view the Smart Grids implementation. This paper aims to develop a new model, determining the minimal set of switches to replace in order to automate the system, along with a senility analysis on the position of the new switches, whether it should be placed in the same place as the manual switch or in a new location. The optimization of the system is made considering the renewable energy sources integration in the grid, energy storage systems simultaneously with the economic and functional requirements of the system, in order to improve the system reliability. The computational tool is tested using the IEEE 119 Bus test system to validate the new tool, where different types of load are considered (residential, commercial and industrial).